Sustainability Initiatives, Knowledge-Intensive Innovators, and Firms’ Performance: An Empirical Examination - Rajesh Kumar Bhaskaran (International Journal of Financial Studies, 2023)
This paper examines the role of sustainability as a major driver of innovation, and assesses its affect on firms’ performance. This study was based on companies listed in the Forbes list of 100 most innovative companies and BCG’s 50 most innovative companies. The innovative sample firms had higher ESG and component scores than the matched control firms, with statistical significance. In terms of distinctiveness of governance, the innovative firms had larger boards, independent board members, higher diversity, and longer board tenure. Innovative firms had superior financial performance in comparison with the matched control firms. A logit regression model was employed to predict whether firms that adopt sustainability initiatives tend also to be innovative companies. Firms with high intensity of investment in social and governance initiatives tended to be innovative. Innovative firms had greater focus on social initiatives related to employee satisfaction, promotion of a healthy and safe workplace, and diversity. However, innovative firms tended to score lower in terms of human rights initiatives. Innovative firms provided superior governance practices for shareholders and effective usage of antitakeover defense mechanisms. Debt-intensive firms tended to be innovative.